Pengaruh Lingkungan Kerja Non Fisik, Insentif dan Pengalaman Kerja terhadap Produktivitas Kerja PT. Sampoerna Alam Samudra - Muhammad Hafidz Arrijal (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out about the effect of non-physical work environment, incentives and work experience on employee productivity at PT. Sampoerna Alam Samudra. Human Resources are needed by the company to maintain, develop and achieve the company's goals so that it does not go out of business, therefore the company must do